An association between the BanI polymorphism of the PLA2G4A gene for calcium-dependent phospholipase A2 and plasma glucose levels among females with schizophrenia. (August 2018) - Nadalin, Sergej; Buretić-Tomljanović, Alena
Highlights: This is the first report on the PLA2G4A gene and glucose and lipid metabolism in schizophrenia. This is the first report on the BanI polymorphism and glucose and lipid metabolism. The BanI polymorphism influences plasma glucose concentration in female patients. The BanI polymorphism does not influence lipid concentration in males. The BanI polymorphism does not influence lipid concentration in females. Abstract: Abnormal glucose and lipid metabolism may be associated with altered cytosolic Ca 2+ -dependent phospholipase A2 (cPLA2) signaling in patients with schizophrenia. The relationship between schizophrenia and the functional BanI polymorphism (rs10798059 variant, A/G polymorphism) of the PLA2G4A gene for cPLA2 has been extensively investigated. We previously reported that it can influence several clinical features of schizophrenia, and it was shown to contribute to schizophrenia risk in several population studies. We performed PCR/RFLP genotyping of 263 Croatian patients (males/females: 139/124) to investigate the relationship between the BanI polymorphism and fasting plasma glucose and lipid levels in patients with schizophrenia. Our results indicate that the BanI polymorphic variant contributes significantly to plasma glucose levels in female patients. Females carrying the PLA2G4A-G allele (PLA2G4A-GG homozygous and PLA2G4A-AG heterozygous) presented with lower glucose levels than PLA2G4A-AA homozygous carriers, and the PLA2G4A genotype contributed approximately 6% of plasma glucose level variability in this group of patients.